2023
DOI: 10.1002/advs.202305950
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Ferroelectric Filaments

Marcell T. Máthé,
Kelum Perera,
Ágnes Buka
et al.

Abstract: Freestanding slender fluid filaments of room‐temperature ferroelectric nematic liquid crystals are described. They are stabilized either by internal electric fields of bound charges formed due to polarization splay or by external voltage applied between suspending wires. The phenomenon is similar to those observed in dielectric fluids, such as deionized water, except that in ferroelectric nematic materials the voltages required are three orders of magnitudes smaller and the aspect ratio is much higher. The obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…FNLC 919 had two nematic phases, N and N 1 above the N F phase with the phase sequence in cooling as I 80 ○ C N 1 44 ○ C N 32 ○ C N F 8 ○ C Cr. FNLC 919 was studied by Yu et al [27] and Máthé et al [28] and the ferroelectric polarization was measured in free-standing threads at room temperature to be P o ≈ 3 • 10 −2 C m −2 . [28] This value was smaller than the P o ≈ 4.7 • 10 −2 C m −2 ,in in-plane field geometry (see Figure 3d) were measured here, likely due to the inhomogeneous field in the free-standing threads.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FNLC 919 had two nematic phases, N and N 1 above the N F phase with the phase sequence in cooling as I 80 ○ C N 1 44 ○ C N 32 ○ C N F 8 ○ C Cr. FNLC 919 was studied by Yu et al [27] and Máthé et al [28] and the ferroelectric polarization was measured in free-standing threads at room temperature to be P o ≈ 3 • 10 −2 C m −2 . [28] This value was smaller than the P o ≈ 4.7 • 10 −2 C m −2 ,in in-plane field geometry (see Figure 3d) were measured here, likely due to the inhomogeneous field in the free-standing threads.…”
Section: Methodsmentioning
confidence: 99%
“…FNLC 919 was studied by Yu et al [27] and Máthé et al [28] and the ferroelectric polarization was measured in free-standing threads at room temperature to be P o ≈ 3 • 10 −2 C m −2 . [28] This value was smaller than the P o ≈ 4.7 • 10 −2 C m −2 ,in in-plane field geometry (see Figure 3d) were measured here, likely due to the inhomogeneous field in the free-standing threads. [28] Both FNLCs were contained between two, parallel glass plates having conducting indium tin oxide (ITO) sputtered in their inner surface, separated by a distance d, which was much smaller than the lateral dimensions (1 − 2 cm) of the planes.…”
Section: Methodsmentioning
confidence: 99%
“…The FNLC substance used in this study was FNLC-919 (Merck) [9][10][11]17]. The original phase sequence is as follows [10]; Iso. 80 °C N1 44 °C N2 32 °C NF 8 °C Cryst.…”
Section: Fnlc Substance and Sample Cell Praparationmentioning
confidence: 99%
“…The emergence of FNLCs challenges this classical understanding, thereby eliciting profound interest in FNLCs from the viewpoints of both material physics and the development of novel applications [8,9]. Recently, the first demonstration of converse piezoelectricity using FNLC substances that exhibit significant ferroelectricity at room temperature was published [10,11], and these results pave the way to the realization of flexible actuators that cannot be realized with solid materials. Studies on the unique electrical attributes of FNLCs have demonstrated that they can be distinguished from ordinary LCs using methods such as temperaturedependent dielectric constant measurements [6,12] and the detection of second harmonic generation [7,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation